Internet Teletraffic Modeling and Estimation - Lima, Alexandre Barbosa de; Amazonas, Jose Roberto de Almeida (River Publishers Series in Information Science and Technology, 2022)
Network traffic has fractal properties such as impulsiveness, selfsimilarity, and long-range dependence over several time scales, from milliseconds to minutes. These features have motivated the development of new traffic models and traffic control algorithms. This book presents a new statespace model for Internet traffic, which is based on a finite-dimensional representation of the Autoregressive Fractionally Integrated Moving Average (ARFIMA) random process. The modeling via Autoregressive (AR) processes is also investigated.